(untitled) (Cambridge, UK, 2001)
This text provides an overview of current and emerging technologies and equipment. The nine contributors represent both academia and industry in the UK. They cover cereal and flour production; wheat, corn, and coarse grains milling; biotechnology, cereal, and cereal product quality; rice, pasta, and Asian noodle processing; breakfast cereals; malting; and breadmaking
Công nghệ sau thu hoạch ngũ cốc,Công nghệ chế biến sản phẩm từ ngũ cốc
Keywords: Cereal products